2017
DOI: 10.1080/20426445.2017.1317471
|View full text |Cite
|
Sign up to set email alerts
|

CLT panels in Japan from cradle to construction site gate: global warming potential and freight costs impact of three supply options

Abstract: This study investigates the effect of three different multimodal transport combinations for cross laminated timber (CLT) supply on global warming potential and freight costs from cradle to the construction site gate. It attempts to demonstrate to what extent a local approach could be beneficial, both environmentally and economically. It was found that emissions during the transportation modules will be more than those from the manufacturing stages in the case of intercontinental routes, contrary to the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The economic allocation may require stable prices of products for a consistent result, which has not occurred in the U.S. [103] reported on the pricing variability tied to economic allocation for wood-based panels. Thus, depending on the products studied, the LCIA results varied a little or a lot as shown by Reference [102] on wood panels. The current PCR for North American Structural and Architectural Wood Products [95] requires economic allocation to be used in LCA studies but the current PCR under revision will fall back to mass allocation partly because of the problem illustrated by Taylor et al [103].…”
Section: Allocation Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…The economic allocation may require stable prices of products for a consistent result, which has not occurred in the U.S. [103] reported on the pricing variability tied to economic allocation for wood-based panels. Thus, depending on the products studied, the LCIA results varied a little or a lot as shown by Reference [102] on wood panels. The current PCR for North American Structural and Architectural Wood Products [95] requires economic allocation to be used in LCA studies but the current PCR under revision will fall back to mass allocation partly because of the problem illustrated by Taylor et al [103].…”
Section: Allocation Approachmentioning
confidence: 97%
“…The study reported that up to a 29% decrease in GW impact can be achieved using a lighter species such as Sitka spruce compared with the baseline scenario (Douglas-fir and western hemlock mix). Another study investigated the effect of logistics, focusing on Japanese logistics [102]. That study revealed that, for shorter distances, ocean freight transportation resulted in lower GW impact compared with truck transportation.…”
Section: Emerging Wood Building Productsmentioning
confidence: 99%
“…The issue of variability associated with distance and modes of transportation is not, however, considered in such a study [14]. Another relevant research by Passarelli et al [16] compared three different multimodal transport combinations in Japan. The results indicate that the GWP of CLT transportation from another continent is higher than the production stage.…”
Section: Introductionmentioning
confidence: 99%